2006
DOI: 10.1248/bpb.29.1880
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Breviscapine on Ischemic Vascular Dementia in Rats

Abstract: With an increase of elderly population, aging-related diseases such as hypertension, arteriosclerosis and different forms of dementia are also increased. 1) One of these diseases is vascular dementia (VD). VD is a step-wise deterioration in intellectual powers that appear as different areas of the brain are damaged by loss of blood supply.2,3) The conventional concept of VD is that of multi-infarct dementia, 3,4) arising from chronic cerebral ischemia and various vascular changes in the brain.5) It is reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…Some studies have found a direct correlation between cerebral hypoperfusion-induced memory deficit and CA1 cell damage (26)(27)(28), and an association of impaired learning performance 3 weeks after the procedure with a significant pyramidal cell loss in the CA1 region (29). However, others have reported no correlation or only a weak one between diminished CA1 neuron number and performance in the Morris maze (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found a direct correlation between cerebral hypoperfusion-induced memory deficit and CA1 cell damage (26)(27)(28), and an association of impaired learning performance 3 weeks after the procedure with a significant pyramidal cell loss in the CA1 region (29). However, others have reported no correlation or only a weak one between diminished CA1 neuron number and performance in the Morris maze (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…Primary rat cortical neurons were isolated as described in our previous study (23,24), with some modifications. Briefly, the cortex of newborn Sprague-Dawley rats were dissected and rinsed in ice-cold Dulbecco's PBS.…”
Section: Cell Culturementioning
confidence: 99%
“…[13][14][15][16] Recently, it is demonstrated that some flavonoids such as hypericum perforatum and quercetin, display antidepressant effects and attenuate the cognitive deficits caused by major depression. [17][18][19] Baicalein (Bai) is one of the most active flavonoids found in the dry roots of Scutellaria baicalensis Georgi.…”
mentioning
confidence: 99%